The effectiveness of using YouTube videos as supplementary materials on enhancing students’ listening skills - A study conducted at International Standard Program, University of Languages and International Studies, Vietnam National University = Tính hiệu - Vi, Diệu Thuần (University of Languages and International Studies, 2017)
M.A. Thesis. English Teaching Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2015